Ursodeoxycholyl Lysophosphatidylethanolamide Protects Against Hepatic Ischemia and Reperfusion Injury in Mice. Issue 4 (April 2015) - Wang, Jiliang; Deng, Xiuling; Yi, Shengen; Pathil, Anita; Zhang, Wujuan; Setchell, Kenneth; Stremmel, Wolfgang; Chamulitrat, Walee
<x xml:space="preserve">Abstract</x> ABSTRACT The ischemia and reperfusion (I/R) injury that occurs during liver transplantation causes severe complications leading to transplantation failure. We have designed a cytoprotective agent, ursodeoxycholyl lysophosphatidylethanolamide (UDCA-LPE), which promotes the survival of cultured hepatocellular cell lines and inhibits apoptosis and inflammation in the in vivo models of liver injury. Here, we show that UDCA-LPE increased the viability of mouse hepatocytes by activating the Akt/glycogen synthase kinase 3β survival signaling pathways. We further tested whether UDCA-LPE could protect hepatic I/R injury in mice by clamping liver lobes of C57/BL6 mice for 90 min of ischemia followed by unclamping and reperfusion for 2 h. Two regimens for UDCA-LPE treatment were carried out; with a single dose of 100 mg/kg UDCA-LPE intraperitoneally injected 30 min prior to ischemia and a double dose of 50 mg/kg UDCA-LPE given 30 min prior to ischemia and just prior to reperfusion. Using histology and liver enzyme determination, we observed that hepatic I/R caused significant hepatic necrosis, which was decreased in UDCA-LPE–treated mice undergoing I/R. Ursodeoxycholyl LPE concomitantly protected against I/R-induced apoptosis (cleaved caspase 3, cleaved poly[ADP-ribose] polymerase 1), inflammation (IL-1β, CD11b, chemokine ligands 2 and 3, chemokine receptor 2), and portal fibrogenesis (α-smooth muscle actin, plasminogen activator inhibitor 1), as determined by Western blot, quantitative real-time polymerase chain reaction, and immunohistochemical analyses. The protection by UDCA-LPE was found to be better in the double-dose than in the single-dose regimen. Thus, UDCA-LPE promoted the survival of mouse hepatocytes and protected against hepatic I/R injury and thus may be of therapeutic use in liver transplantation settings.